Prospective mathematics teachers’ understanding of proof in mathematics for high school - Mirza, Ade; Fitriawan, Dona; R, Zubaidah; Nursangaji, Asep (Universitas Islam Raden Intan Lampung, INDONESIA, 2022)
Changes in the mathematics education curriculum affect the preparation of prospective teachers to learn as well as possible and provide extensive opportunities and experiences regarding mathematical proof in secondary schools, especially those reflecting the nature and role of proof in the field of mathematics. Teachers' ability to respond to this depends on their understanding of proof in a mathematical context. This research examined the understanding of 36 prospective mathematics teachers at Tanjungpura University regarding proof and their ability to prove problems in the context of high school mathematics. The data were collected through a series of interviews focused on their responses to the role of proof and from tests to prove math problems. This research is descriptive-analytical research, which describes the conception of prospective mathematics teachers as knowledgeable in mathematics about proof. However, some view proof as a tool for studying mathematics. This research also found that many of them had a limited view of the nature of proof. They lacked a clear understanding of the subject of demonstrating or explaining the process of proving a mathematical statement.